An Empirical Investigation in Delivering Quality Healthcare Services to Patients - Mir, Parvez A. (Indian Journal of Marketing, 2011)
Healthcare industry in the current scenario is becoming a burgeoning industry, attracting domestic as well as foreign clientele because it offers world-class state of the art medical facilities at competitive prices. However, in this profit-oriented approach, the poor are left in the lurch, as they are mostly dependent on public sector hospitals. This research paper identifies the different dimensions of SERVQUAL to evaluate the perception of patients towards hospitals services. The paper also suggests adoption of a balanced approach to promote healthcare industry as an incentive to boost medical tourism as well as taking care of the poor also.